Racjonalna jednostka w odczarowanym mieście - Kędzierski , Maciej (Studia Europaea Gnesnensia, 2018)
The chief aim of reflection in this paper is to outline the image of rational cities and their products, including the consumerist superstructure. By way of conclusion, the author uses the example of the Warsaw borough of Służewiec-Przemysłowy (colloquially known as Mordor) to illustrate the transformation of the concept of rational reality.